The association between menstrual cycle phase, menstrual irregularities, contraceptive use and musculoskeletal injury among female athletes: a scoping review - MacMillan, C.; Olivier, B.; Viljoen, C.; van Rensburg, D. C. J.; Sewry, N. (Sports Medicine, 2024)
Background: The influence of menstrual cycle phases (MCPs), menstrual irregularities (MI) and hormonal contraceptive (HC) use on injury among female athletes has been scrutinised. Existing systematic reviews investigating the effect of exposures affecting the endogenous reproductive hormone status on sporting injuries are limited in terms of the types of studies included and injuries investigated. Objective: This scoping review aims to summarise the coverage of the literature related to the extent, nature and characteristics of the influence of MCP, MI and HC use on musculoskeletal injuries among athletes. It also aims to summarise key concepts and definitions in the relevant literature. Observational and experimental studies investigating the effect of MCP, MI, and HC on musculoskeletal injuries among female individuals of reproductive age were included. Studies specifically stating pregnant women, perimenopausal/postmenopausal athletes, or those using medication (other than HC) that affects reproductive hormone profiles or the musculoskeletal system were excluded. Methods: This scoping review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping reviews and JBI scoping review guidelines. Published and unpublished studies were sourced from several databases and resources. Initial keywords used included terms related to "menstrual cycle", "hormonal contraception" and "injury." Titles and abstracts of identified citations were screened independently and assessed for eligibility by two independent reviewers. Data from the included studies were extracted using a standard data extraction form. Results: The search yielded 10,696 articles, of which 96 met the eligibility criteria. Most studies investigated MI (77%), and 49% included MCP as a contributing injury risk factor. Publications have increased over the last two decades. Collectively, only 16% of research has been conducted in Africa, Asia and Oceania. There were no studies from South America. Seventy-five percent of the studies investigated individual versus team (25%) sport athletes. Most studies only investigated elite or professional (n = 24; 25%) level athletes. The definitions of injury, eumenorrhea and MI differ vastly among studies. Regarding MI, most studies (69%) investigated secondary amenorrhea, followed by oligomenorrhea (51%) and primary amenorrhea (43%). Concerning HC, the influence of oral contraceptive pills was mainly investigated. Conclusions: Research related to MCP, MI and HC as contributing musculoskeletal injury risk factors is increasing; however, several gaps have been identified, including research from countries other than North America and Europe, the study population being non-professional/elite level athletes, athletes participating in team sports and specific injuries related to MCP, MI and HC, respectively. Differences in methodology and terminology of injury, MCP and MI hinder comparative summative research, and future research should consider current published guidelines during the study design. Identifying barriers to following standard guidelines or research investigating the most practical yet accurate methods to investigate the influence of MCP on musculoskeletal health might yield valuable insights for future research designs.